VD_FINDINFO HC / 2018 / 745 vom 14. September 2018 - VD Tribunal cantonal (2018)
DIVORCE, LIQUIDATION DU RÉGIME MATRIMONIAL, SOCIÉTÉ SIMPLE, APPORTSOCIÉTÉ | 530 al. 1 CO, 531 CO, 308 al. 1 let. a CPC (CH)